(3GdMOhO(B:s (3efGWb JeGS hUQGY Ce LShQ JcGed hGfOeGL? (B/s - (3HNhT(B, (3eUWais ((3CHhXHj (B- (3OhdI GdGeGQGJ GdYQHjI GdeJMOI(B:s (3eQcR GdGeGQGJ ddOQGSGJ hGdHMhK GdGSJQGJjLjI(B,s, 2022)
(3JgOa GdOQGSI Edi efGbTI ecGfI GdMOhO aj Xd GdJMhdGJ GdOhdjI GdQGgfI GdJj JTgO fbGkTG MGkqOG HTCf eSCdI GdgLQI ef LgI, hGdfRYI GdMeGFjI GdJj RGO ajQhS chQhfG GdeSJLO (B((3chajO(B-19) (3ef MOJgG aj Xd GdELQGAGJ GdJj GJNPJgG eYXe Ohd GdYGde HEZdGb MOhOgG efkYG dGfJTGQg ef LgI KGfjI(B. (3dJHQR GdMOhO COGkI eQcRjkI egekI JSJNOegG GdOhd dVeGf UMI ehGWfjgG hQaGgjJge, hdJCNP CHYGkOG CefjI hUdJ aj HYV GdOhd Edi MO EYdGf MGdI GdWhGQF(B. (3hcPdc Gdhbha Ydi OhQgG aj Xd GdKhQI GdJj jTgOgG bWGY GdGJUGd hGdehGUdGJ GdJj CSbWJ GdMhGLR Hjf eNJda GdTYhH hbQHJ GdeSGaGJ(B. (3hJJfGhd GdOQGSI XGgQI GdMOhO ef RGhjnJjf JHOhGf dChd hgdI eNJdanJjf heJfGbVnJjf, dcfgeG aj GdMbjbI JYcSGf Cj MQcI eJcGedI heJLGfSI, eMcheI Heaghe GdeUdMI eMOkOG dSdhcjGJ GdOhd hHGbj GdLgGJ GdaGYdI GdCNQi, GdJj CfJLJ eG HGJ jYQa Gdjhe HKfGFjI GdYhdeI(B/(3GdEbdjejI(B: (3GdRGhjI GdChdi gj RGhjI GdLZQGajG GdSjGSjI GdJj JWQM ehVhY GdMOhO fJGkLG dJQJjHGJ SjGSjI JYcS YdGbGJ GdbhI GdbGFeI Hjf eNJda GdLgGJ GdaGYdI GdOhdGJjI, hJHMK aj GdQhGHW GdLZQGajI dEYGOI gfOSI GdYdGbGJ GdOhdGJjI, GdJj JJeXgQ aj cd eQI HTcd JShjGJ JCNP Tcd eYGgOGJ hGJaGbjGJ, de JQGYj GdJhRjY GdghjGJj Ydi GdCQV HbOQ eG QGYJ GdeUGdM aj gfOSI MOhO GdOhd; CeG GdRGhjI GdKGfjI agj RGhjI GdLZQGajG GdGbJUGOjI, GdJj JDcO JRGjO YdGbGJ GdJcGed hJSGQYgG, GdJj CfJLJ eLJeYGJ eJOGNdI heJUd HYVgG HHYV aj Ref GdYhdeI hGdEfJQfJ GdJj CRGdJ GdMOhO hWhQJ THcGJ eJfhYI, hLYdJ GdJhGUd hGdGfJbGd HGdUhJ hGdUhQI CekQG SgkdG jJbfg GdCWaGd bHd GdcHGQ(B.s
Keywords: (3GdMOhO GdLZQGajIs; (3GdMOhO GdSjGSIs; (3GdMOhO GdOhdjIs; (3GdYdGbGJ GdOhdjIs